Social Status Moderates the Relationship Between Facial Structure and Aggression - Goetz, Stefan M. M.; Shattuck, Kraig S.; Miller, Robert M.; Campbell, Jocelyn A.; Lozoya, Elianna; Weisfeld, Glenn E.; Carré, Justin M. (Psychological Science, 2013)
A growing body of evidence has linked individual differences in facial structure—in particular, the facial width-to-height ratio (FWHR)—to social behaviors, including aggression, cheating, and nonreciprocation of trust. In the research reported here, we extended this work by demonstrating that the association between FWHR and aggression is moderated by subjective and objective measures of social status. In Study 1 ( N = 237 college students), FWHR was positively correlated with aggressive behavior, but only among men reporting relatively low social status. In Study 2 ( N = 891 professional hockey players), FWHR was positively correlated with penalty minutes, but only among players who earned relatively low salaries. Collectively, these studies provide compelling evidence for the role of social status in moderating the relationship between facial structure and aggression, indicating that FWHR is a robust predictor of aggressive behavior, but only in the context of relatively low social status.